PEMILIHAN PENGRAJIN TERBAIK DENGAN METODE ELECTRE DAN TOPSIS MENGGUNAKAN GUI MATLAB (STUDI KASUS : PT. Asaputex Jaya, Tegal) - Hafii Risalam; Rita Rahmawati; Suparti Suparti (Jurnal Gaussian, 2016)
Company is technical unity that aims to produce goods services. One of determinants of succesful company is its human resources or known as employees. PT. Asaputex Jaya is one of company that enganged in the manufacture of sarong. Poor quality of human resources, especially on the production is still an obstacle for PT. Asaputex Jaya. Therefore selection of the best craftsmen need to be done so that production process doesn’t meet any probelms. This research was conducted to determine top craftsmen in sarong production on PT. Asaputex Jaya, and also used for PT. Asaputex Jaya’s human resources management interests. ELECTRE is based on rankings concept through pair comparison between alternatives on the suitable criteria. While TOPSIS can determine the value of preference for each alternative, the concept is simple and easy to understand. There are 8 criteria in the selection of top craftsmen: design, fabrics assembly, merger with filler material, manufacture of sarong, punctuality, statutes of size, tailoring results, and neatness or stitching cleanliness. Through the TOPSIS method selected 10 top craftsmen: 5th, 14th, 15th, 9th, 3rd, 13th,6th, 20th, 18th, and 10th , which then only one top craftsman will be chosen using the ELECTRE method. This study also produced a GUI Matlab programming application that can help users in performing data processing using TOPSIS and ELCTRE to select the best craftsmen on PT. Asaputex Jaya Keyword: SDM, TOPSIS, ELECTRE, GUI Matlab, top craftsmen